“Chemical-Free” and “Organic” Claims in the Age of E-Commerce: Law, Science, and Consumer Protection in India (Maharaja Surajmal Institute Law Journal, 2026)
The rise of concepts such as ‘Chemical-Free’ and ‘Organic’ found on e-Com merce Platforms within India reflects the increasing tension between the expectations of consumers, scientific fact, and the regulatory authority of these terms. The areas of inquiry related to the definition, regulation, and operation of a product as chemical-free and/or organic will be examined under three main areas of law: Statutory Definition and Regulation of Chemicals in Foodstuffs as contained in The Food Safety and Standards Act of India, Statutory Definition of and Protection of Consumers from Misleading Advertising and Marketing as defined in The Consumer Protection Act of India, and Statutory Definition and Regulation of Drugs and Cosmetics as set out in The Drugs and Cosmetics Act of India. Additionally, the investigation will review additional regulatory issues, including the certification/authority of organics and regulators of organic food products, and the entities that regulate their production and marketing. The lack of clear regulation has resulted in an unchecked grey marketing operation; therefore, these corporations are entitled to represent their prod ucts as ‘Ecologically Sustainable’, ‘Eco-Friendly’, or ‘Green’ under Federal Law without providing evidence that supports those claims. This part will also examine scientific definitions and principles of chemically free claims and how courts have applied those definitions and principles in determining whether or not a company has made misleading advertising or has engaged in deceptive comparative advertising practices. Finally, the entity producing these claimed ‘Chemical-Free’ or ‘Organic’ prod ucts will use both Environmental and/or Health-Based Terms in their adver tising to support their claims. In formulating the company’s advertising, they may also make Deliverable and/or Intended Environmental and/or Health Claims to consumers who are likely to rely upon such claims in making their purchasing decisions.
Keywords: Chemical-free claims; Organic food regulation; Green mar keting; Misleading advertisement; Consumer protection; Food Safety and Standards Act, 2006; Consumer Protection Act, 2019